EPID-23. THE PAKISTAN BRAIN TUMOR EPIDEMIOLOGY STUDY: PAVING THE WAY FOR A NATIONAL BRAIN TUMOR REGISTRY. (12th November 2021) - Shah, Mashal; Baig, Erum; Bajwa, Mohammad Hamza; Laghari, Altaf Ali; Bin-Anis, Saad; Akhunzada, Naveed Zaman; Gilani, Jaleed; Jawed, Noyan; Khalid, Usman; Qadeer, Namra; Lutfi, Areeb; Tahir, Izza; et al.
Abstract: INTRODUCTION: In Pakistan, brain tumor epidemiology has been examined in single-centre studies or as part of general cancer registries, which are limited by catchment area, age group, or are not specific to brain tumors. The Pakistan Society of Neuro-Oncology conducted a nationwide study to assess the distribution of brain tumor distribution and associated risk factors. This unfunded study explores data from across Pakistan and serves as a potential model for LMICs to emulate. METHODS: A cross-sectional study was designed to include patients diagnosed with brain tumors in major neurosurgical centers in Pakistan retrospectively from January-December 2019. Patients, both alive and deceased, with a radiological diagnosis of a brain tumor were included. Data were recorded on a comprehensive online form from 35 centers, encompassing an estimated 85% of all the brain tumor patients seeking initial treatment by a neurosurgeon from the public and private sectors. Data collection was split into three regions: Sindh and Balochistan; Punjab; and Khyber Pakhtunkhwa and Islamabad. Data collection occurred between August 2020 and January 2021. RESULTS: A total of 2750 brain tumor cases were recorded of which 1897 (69%) were diagnosed in the private sector hospitals. MRIs were a more common radiological study compared to CT scans. 2666 surgeries were performed, 174 individuals underwent chemotherapy and 479 underwent radiation therapy; approximately two-thirds of the patients that require adjuvant treatment are not able to receive it. Gliomas were the most common tumor, while pineal tumors were the least common. Findings indicate a low metastasis frequency and few females seeking care. CONCLUSION: The study shows that brain tumors are mostly diagnosed and operated on in the private sector; the public sector should be more engaged. The study also highlights that despite inconsistencies in hospital records for brain tumor patients, reliable information can be collected in LMIC settings.